Digital Financial Literacy and Decision-Making: A Behavioural Management Model for Digital Natives - Goso, Goso; Jasman, Jumawan; Husmaruddin, Husmaruddin; Alam, Syamsu (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study develops an integrative behavioral framework to examine how digital financial literacy (DFL) influences financial decision-making among digital-native cohorts. The analysis extends existing behavioral models by incorporating risk tolerance and fintech trust as mechanisms shaping investment, consumption, and saving choices. Using a mixed-method design with 500 survey responses and 30 interviews, the study shows that DFL alters decision patterns in ways mediated by both confidence and caution. A paradox emerges: high trust in fintech often coexists with weak awareness of digital risks, underscoring tensions between literacy and reliance. The findings highlight that financial institutions and policymakers must balance accessibility and innovation with safeguards that foster prudent behavior in digitally native populations.